In vitro evaluation of drug release and antibacterial activity of a silver-loaded wound dressing coated with a multilayer system - Mogrovejo-Valdivia A. (2019)
This research was funded by FONDECYT-CONCYTEC (grant contract number 238-2015-FONDECYT). We want to acknowledge Dr Marco Lopez from INSERM U1008 for SEM analyses.